Validation of practical notebook Morphophysiology IV - Rafael Capote Martínez; Marcia Leticia Gómez García; Quinley Quintana Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2012)
Since the implementation of the Morphophysiology, 2007-2008 academic year, has shown a low achievement and motivation of students in individual and independent study. Most of them do not possess the skills or general intellectual development freelancing enough to assimilate the great independence required by this new learning model. Therefore, it was decided to introduce a new medium of instruction notebook handy morphophysiology IV which is an orientation guide for individual and independent study of students at the same time improves the management process of the educational process, whose usefulness is intended to validate. They surveyed 345 (94.8%) who choose different specialties including Physical Culture. It was used in the survey, the questionnaire technique questions and answers, the closed first, and combining the direct and indirect, with some filter. This study was conducted through the comparison test of proportions between independent samples, using the Microstat statistical system, with a significance level of α = 0.05 (P <0.05). The 97.33% and 95.6% of students classified as necessary and useful respectively, the Practical Notebook, based on teaching assignments. The 67.84% of students suggests that the effectiveness of Practical Notebook is achieved when it is developed in a coordinated manner from staff student effort, reflections set out in groups or teams of study and the guiding role and facilitator professor, where it appears that forces develop participatory techniques. It is concluded that the Practical Notebook, acts as a methodological guide guiding, and developed through teaching assignments by students during individual and independent study, represents an effective tool for the learning process, contributing significantly to the improvement morphophysiology the curricular discipline.